The Next Pandemic: Preparing for Future Global Health Threats - Ermelinda da Costa Monteiro; Joaquim Pinto (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to conduct a systematic review of global health preparations in facing future pandemics. By following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, relevant articles were collected from international databases such as PubMed, Web of Science, and Scopus. The review results show that the COVID-19 pandemic has highlighted the lack of global health preparedness and emphasized the importance of comprehensive preparedness planning, effective early detection systems, and adequate resource allocation. The implications of this research are the importance of increasing international cooperation, investment in research and development, and improving health infrastructure and resources to strengthen global health preparedness in the future.